2007
DOI: 10.1038/sj.leu.2404903
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of risk-based therapy for infant acute lymphoblastic leukemia with or without an MLL gene rearrangement, with emphasis on late effects: a final report of two consecutive studies, MLL96 and MLL98, of the Japan Infant Leukemia Study Group

Abstract: We evaluated the efficacy of a treatment strategy in which infants with acute lymphoblastic leukemia (ALL) were stratified by their MLL gene status and then assigned to different riskbased therapies. A total of 102 patients were registered on two consecutive multicenter trials, designated MLL96 and MLL98, between 1995 and2001. Those with a rearranged MLL gene (MLL-R, n ¼ 80) were assigned to receive intensive chemotherapy followed by hematopoietic stem cell transplantation (HSCT), while those with germline ML… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
125
1
10

Year Published

2008
2008
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 128 publications
(142 citation statements)
references
References 27 publications
5
125
1
10
Order By: Relevance
“…11,12 In a recent report from the Japan Infant Leukemia Group (MLL96 and MLL98 trials), the efficacy of an MLL-based stratifying treatment strategy involving HSCT for all infants with MLL ϩ ALL was evaluated. 10,21 The 5-year EFS rate was only 38.6% for MLL ϩ ALL, which, however, was an improvement compared with historical controls. Notably, of 80 MLL ϩ infant cases, 27 of 49 events occurred before HSCT (mostly early bone marrow relapses); and of 22 of 49 events that occurred after HSCT, 8 were the result of toxic deaths.…”
Section: Org Frommentioning
confidence: 89%
See 1 more Smart Citation
“…11,12 In a recent report from the Japan Infant Leukemia Group (MLL96 and MLL98 trials), the efficacy of an MLL-based stratifying treatment strategy involving HSCT for all infants with MLL ϩ ALL was evaluated. 10,21 The 5-year EFS rate was only 38.6% for MLL ϩ ALL, which, however, was an improvement compared with historical controls. Notably, of 80 MLL ϩ infant cases, 27 of 49 events occurred before HSCT (mostly early bone marrow relapses); and of 22 of 49 events that occurred after HSCT, 8 were the result of toxic deaths.…”
Section: Org Frommentioning
confidence: 89%
“…8 Moreover, possible long-term adverse effects of the preparative regimen before and of graft-versus-host disease (GVHD) after HSCT, disturbing the physical development in such a young and vulnerable patient population, demand for a very strict indication only left for infants with a predictably very poor chance to maintain first remission with chemotherapy alone. 9,10 In the first large international multicenter trial for the treatment of infant ALL, Interfant-99, allogeneic HSCT was a possible option (but not mandated) for patients with initially poorly responding leukemia, defined by a poor response to steroids at day 8 of chemotherapy. 6 However, no significant benefit of HSCT was observed in this cohort of high-risk patients when disease-free survival (DFS) was adjusted for the waiting time to HSCT.…”
Section: Introductionmentioning
confidence: 99%
“…7 Approximately 20% of the infant ALL patients carry germline (or wild-type) MLL genes, and nowadays have a far better prognosis with event-free survival chances of 75% to 95%. 7,11 Multiple microarray studies demonstrated that MLL translocations specify a distinct gene expression profile that is clearly distinguishable from other ALL subtypes and from acute myeloid leukemia (AML). [1][2][3]12,13 Moreover, Zangrando et al recently reported a gene expression signature commonly shared by MLLrearranged ALL and AML patients, identifying dysregulated genes specifically associated with the MLL translocation, irrespective of the type of leukemia.…”
Section: Introductionmentioning
confidence: 99%
“…The eventfree survival of infant ALL is exceptionally low (45-50%), when compared with older children with ALL (B80%). 1,[3][4][5][6] The MLL rearrangement as a first, prenatal leukemogenic event has been elegantly shown to occur in utero by Ford and colleagues. 7 Although the same is true for other types of leukemia, the far shorter latency to leukemia in infant ALL compared with older children, and the exceptionally high concordance rate for ALL in monochorionic twins, 8 indicate that the sole MLL fusion gene could be sufficient for overt leukemia development.…”
Section: Introductionmentioning
confidence: 99%